Vowel production in two occlusal classes - Araújo, André (2007)
The influence of occlusal class in speech production has been studied using the X-ray Microbeam Speech Production Database (XRMB-SPD). The objective of the study was to relate the occlusal classes I and II with vowel production adaptations. The “Modified A-Space” method was used to select 4 speakers (1 class I male, 1 class I female, 1 class II male and 1 class II female). Articulatory and acoustic features of the vowels [i, {, A, u] were studied using different tasks and methods. Results show some structural differences related with occlusal class and variance in class II subjects’ structures and articulatory adaptations. The major differences found in the vowels’ formants were between male and female groups. Occlusal class also seems to influence acoustical features of vowels produced by female speakers. Structural differences were found, but subjects showed a high adaptation capacity, being able to adjust their articulators to produce all vowels.